Individual and Relationship Factors Associated With the Self-Identified Inability to Experience Orgasm in a Community Sample of Heterosexual Men From Three European Countries. Issue 3 (2nd April 2016) - Carvalheira, Ana; Santana, Rita
Abstract : The inability to reach orgasm is probably the least common and least understood of all male sexual dysfunctions. The present study aims to investigate the incidence of the inability to reach orgasm, and the psychological and interpersonal factors associated with this sexual difficulty. A total of 3, 672 heterosexual men from three European countries (1, 937 Portuguese, 1, 215 Croats, 520 Norwegians) participated in this web survey ( M age = 36.6 years, SD = 18–75 years). A total of 354 (9.6%) reported the inability to reach orgasm. Among those men, 89.8% reported moderate to extreme distress regarding this sexual difficulty. A multivariate assessment revealed that men in short-term relationships and taking antidepressants were more likely to report inability to reach orgasm. Men who reported having difficulties getting or maintaining an erection were 4 times more likely to have experienced the inability to reach orgasm than were those who did not report this difficulty. Men who experienced difficulty "'letting go' and surrendering to sexual pleasure during sex" were 2.7 times more likely to have experienced the inability to reach orgasm than were those who did not report this difficulty. This difficulty of "letting go" might reflect the unwillingness to give oneself, an idea presented in previous research.